IMPLEMENTASI KEBIJAKAN PAJAK SARANG BURUNG WALET DI KOTA PALU - M. Kafrawi Al- Kafiah Samsu; Yulizar Pramudika Tawil; Risma Ariyani; Muzakir Tawil; Samsu A Sahibo (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Local taxes and levies have an important role to encourage regional development, and increase regional income in the context of the welfare and prosperity of the people. In addition, with this Regional Regulation, it is expected that there will be an increase in public awareness of fulfilling tax and levy obligations (Year-2015-study-of-potential-management-of-Palu-city-2015, n.d.). Swallow Nest Tax is one of the important sources of local revenue to finance the administration of Government, Implementation of development, and Community development. Referring to the Regional Regulation of Palu City Number 1 of 2011 concerning Regional Taxes. Article 68 paragraph (1) The object of Swallow's Nest Tax is the collection and/or exploitation of Swallow's Nest. And article 69 paragraph (1) Swallow Nest Tax Subjects are individuals or entities that take and/or operate Swallow Nests.The objectives of this research are: To find out the implementation of the swallow's nest tax policy in Palu City. The research design used descriptive qualitative. This research is designed within one year.